The problem of integrating Gender Studies and business ethics fields - M.-M. Lyubivaya (Ukrainian Cultural Studies, 2022)
Business ethics is a branch of applied ethics that examines ethical principles and moral issues in or caused by business. Like other branches of applied ethics, business ethics has both a descriptive and a normative element. In its descriptive function, business ethics most often connects the work of the business world with the processes of markets, economic growth, profit, technological achievements, as well as the practice of organization and management. In its normative use, the business of business ethics is the study of the structures, policies, and principles that underlie the often taken-for-granted descriptive aspects of the business world and the associated behavior of individuals and organizations.
Keywords: gender studies